Motives for thermal tourism: an application to North and Central Portugal - Brandão, Filipa (2021)
Health and wellness tourism should be particularly valued in the post-pandemic phase. It has the potential to be a strategic product that enhances the population’s well-being and quality of life, on social, physical, and environmental levels. Different proposals for specialized experiences that complement what the destination offers allow to position regions as health and wellness destinations. Thermal tourism should thus be encouraged as a specific product designed on the innovation and diversification observed in the related services and the benefits recognized for all ages. Considering the relevance of thermal springs and thermal tourists for the image, positioning, and development of touristic destinations, this research aims to identify the specific motivations of tourists that attract them to the practice of thermal tourism, to understand how the benefits for which thermal tourists search and their sociodemographic profile influence the motivations of tourists, and how those motivations determine the characteristics of travel. This research was developed on the North and Centre of Portugal for their relevance in the context of thermal springs and related touristic activities. To achieve the research objectives, a questionnaire survey was conducted among thermal tourists, through a non-probability by convenience sampling, using bivariate tests, such as Pearson’s chi-squared test, one-way ANOVA, and t-Student test. The results highlight that most respondents practiced thermal tourism due to leisure and relaxation benefits, such as the escape from daily stress, spend time with family, and being “pampered”; relaxation is the most valued motivation, followed by the search for psychological and physical well-being. The research found relations between the benefits expected by thermal tourists and their travel characteristics, such as the composition of the group, the general travel motivation, the chosen thermal destination, and the number of nights spent at the location. In thermal tourism, new challenges emerge, demanding the development of strategies, products, and services that respond to the needs of specific market sections.